Suppression of T Cell Autophagy Results in Decreased Viability and Function of T Cells Through Accelerated Apoptosis in a Murine Sepsis Model*. Issue 1 (January 2017) - Oami, Takehiko; Watanabe, Eizo; Hatano, Masahiko; Sunahara, Satoshi; Fujimura, Lisa; Sakamoto, Akemi; Ito, Chizuru; Toshimori, Kiyotaka; Oda, Shigeto
Abstract : Objective: While type 1 programmed cell death (apoptosis) of T cells leads to immunosuppression in sepsis, a crosstalk between apoptosis and autophagy (type 2 programmed cell death) has not been shown. The aim of this study is to elucidate the details of the interaction between autophagy and immunosuppression. Design: Laboratory investigation in the murine sepsis model. Setting: University laboratory. Subjects: Six- to 8-week-old male mice. Interventions: We investigated the kinetics of autophagy in T cells from spleen in a cecal ligation and puncture model with green fluorescent protein-microtubule-associated protein light chain 3 transgenic mice. We analyzed apoptosis, mitochondrial homeostasis and cytokine production in T cells, and survival rate after cecal ligation and puncture using T cell–specific autophagy-deficient mice. Measurements and Main Results: We observed an increase of autophagosomes, which was assessed by flow cytometry. However, an autophagy process in CD4 + T cells during sepsis was insufficient including the accumulation of p62. On the other hand, a blockade of autophagy accelerated T cell apoptosis compared with the control mice, augmenting the gene expression of Bcl-2-like 11 and programmed cell death 1. Furthermore, mitochondrial accumulation in T cells occurred via a blockade of autophagy during sepsis. In addition, interleukin-10 production in CD4 + T cells from the cecal ligation and puncture–operated knockout mice was markedly increased. Consequently, deficiency of autophagy in T cells significantly decreased the survival rate in the murine sepsis model. Conclusions: We demonstrated that blocking autophagy accelerated apoptosis and increased mortality in concordance with the insufficient autophagy process in CD4 + T cells in the murine sepsis model, suggesting that T cell autophagy plays a protective role against apoptosis and immunosuppression in sepsis. Abstract : Supplemental Digital Content is available in the text.